Pengaruh Kepemimpinan Direktur Terhadap Loyalitas, Kinerja, Kedisiplinan Karyawan (Dosen Dan Tenaga Kependidikan) AKJPII Pekanbaru - Anna Maria; H Hartini (Jurnal HUMMANSI (Humaniora, Manajemen, Akuntansi), 2019)
The role of director becomes one of determining factors for success rate of a program and college management. Leadership theory characterizes two roles in leadership process: task-oriented and relationship-oriented leadership behaviors. Therefore, a study on the effect of director’s leadership on loyalty, work performance, and discipline among employees (lecturers and staffs) at AKJP II Pekanbaru was conducted. The research results using managerial grid indicatedthat the director of AKJP II applied both task-oriented leadership and relationship-oriented behavior at (coordinate) 8.9. This quadrant signifies director’s accomplishment is obtained by giving freedom to employees, and responded by working through the specified standard as their respect to director. The effect of director’s leadership was analyzed with linear regression analysis. Correlation analysis showed significant and positive correlation. Director significantly affected employees’ loyalty, work performance, and discipline at the rate of 0.031, 0.049, and 0.023 respectively with 33,1%, 28.5%, and 36.1% in percentage of effect.